Implementation of Islamic Spiritual Guidance in Growing Work Ethic for Employees at JNE Tangerang Office: ENG - Salsabila salsabila; Terra Nurlatipah; Wahyunengsih wahyunengsih (Jurnal al-Shifa Bimbingan Konseling Islam, 2022)
This research is entitled Implementation of Islamic Spiritual Guidance in Fostering Work Ethic for Employees at the JNE Office of Tangerang Center. Islamic Spiritual Guidance is an aid carried out by experts in Islamic Spirituality that can help arouse the spirit and spiritual motivation of the religion. This study aims to analyze and implement Islamic spiritual guidance models in fostering employees' work ethics at the JNE office. The study methods used data collection techniques with interviews and secondary data obtained from employees of JNE Tangerang, book sources, and journals. The participants involved were the Chairman of the Spiritual Department of JNE Tangerang and several employees of the JNE Tangerang office. This study shows that the process of Islamic spiritual guidance services at the JNE Tangerang Office is carried out in several stages, namely: starting from providing guidance related to the tadarus Qur'an, providing flashes of interpretation, and providing fiqh guidance. Islamic spiritual guidance services foster employee work ethic in material delivery. The delivery of the material by carried out, giving awareness to all employees of JNE Tangerang that as a Muslim beside him, he has the mandate to work contract. Of course, Islamic religious values should not be left behind.